Accuracy of Fibrosis-4 index and non-alcoholic fatty liver disease fibrosis scores in metabolic (dysfunction) associated fatty liver disease according to body mass index: failure in the prediction of advanced fibrosis in lean and morbidly obese individuals - (:unkn) unknown (My University, 2022)
BACKGROUND AND AIM: While non-invasive scores are increasingly being used to screen for advanced fibrosis in metabolic (dysfunction) associated fatty liver disease (MAFLD), the effect of BMI on their clinical utility remains uncertain. This study assessed the usefulness of the Fibrosis-4 index (FIB-4) and the non-alcoholic fatty liver disease fibrosis score (NFS) in lean, overweight, obese, severely obese, and morbidly obese patients with biopsy-proven MAFLD. METHODS: A total of 560 patients (28 lean, 174 overweight, 229 obese, 89 severely obese, 40 morbidly obese) were included. Diagnostic performances and optimal cut-off values for FIB-4 and NFS were calculated using receiver operating characteristic (ROC) curve analysis. RESULTS: In both lean and morbidly obese patients with MAFLD, both FIB-4 and NFS failed to discriminate advanced fibrosis. Conversely, both scores showed acceptable diagnostic performances in exclusion of advanced fibrosis in overweight, obese, and severely obese patients. FIB-4 was able to exclude advanced fibrosis with the highest diagnostic accuracy in the subgroup of overweight patients (area under the ROC curve: 0.829, 95% confidence interval: 0.738-0.919). CONCLUSION: FIB-4 and NFS can confidently be used to exclude advanced fibrosis in overweight, obese, and severely obese patients. However, they do not appear clinically useful in lean and morbidly obese patients.